”Hvid udenpå. Indeni er jeg helt ... grå”. Hybride identiteter i Jakob Ejersbos ”Afrika-trilogi” - Schab, Sylwia Izabela (Versita, 2012)
The aim of the article is to discuss the problem of hybrid identity, as it is presented in Jakob Ejersbo’s “Africa-trilogy” (2009). As the methodological framework for the analysis serve some of the main notions borrowed from postcolonial studies (as hybridity and contact zone), as well as Zygmunt Bauman’s diagnoses on “the liquid modernity” (among others his understanding of identity and his tourist and vagabond metaphors). The latter ones indicate the universal dimension of Ejersbo’s prose, which until now has been read mainly from the postcolonial critique’s position and as a polemical comment on the Scandinavian self-understanding as a region, which has never been included in the colonial project and which sets an example on providing humanitarian aid.
„White Outside. Inside I am Completely… Grey.” Hybrid Identities in Jakob Ejersbo’s “African-Trilogy”
Keywords: Det hybride; Identitet; Jakob Ejersbo; Afrika-trilogi; Kontaktzone; Flydende modernitet; Hybridity; Identity; Africa-trilogy; Contact zone; Liquid modernity